Promotion of Short Rotation Agro and Farm Forestry System in Gujarat and Maharashtra by JK Paper Limited Unit-CPM - Agarwal, N. K.; Shukla, O. P.; Narkhede, S. L.; Chauhan, S. K. S. (Indian Forester, 2017)
JK Paper Ltd. Unit: CPM has put in pioneering efforts and working with the farming communities in Gujarat and Maharashtra for meeting its raw material requirement by promoting short rotation pulpwood agro and farm forestry plantations on their farm lands. This has created a win-win relationship for farmers as well as industry by helping farmers realize value from their wastelands and helping industry meet its ever increasing demand for raw material on a sustainable basis. Farmers all over India appreciate the multifarious benefits from trees and they have for decades maintained sporadic naturally grown trees on their farms. Mostly land owners prefer to lease their lands on annual basis instead of growing trees adopting short rotation farm forestry farming. Yet farmers have amply demonstrated, as in the case of clonal eucalyptus plantations that many of them are keen to opt for agro-forestry plantations if there are major benefits and substantially higher returns from this option. Some of the most important considerations which facilitate farmers to take positive decision in favour of Farm- forestry as a preferred land use option are high productivity and far better returns compared to agricultural crops. This system has gradually accepted and replacing sugarcane crop by farmers because it was less labour-intensive and labour requirements over the year. Tree farming with eucalyptus has now become so popular that irrigated and fertile land to the farmers in Gujarat. JK Paper unit- CPM is producing high productive, disease resistant and site specific clones of Eucalyptus, Leucaena and Casuarina to the tune of 10 Million per annum and provides technical guidance for planting and maintenance and provides assured buy back of wood at prevailing market price. Till date we have covered about 50000 ha of land under farm forestry plantations of Leucaena, Eucalyptus and Casuarina in Gujarat and Maharashtra.